Joint Beamforming and Channel Reconfiguration for RIS-Assisted Millimeter Wave Massive MIMO-OFDM Systems - Wang, Hanyu; Fang, Jun; Li, Hongbin (IEEE transactions on vehicular technology, 2023)
In this paper, we consider the problem of joint active and passive beamforming for reconfigurable intelligent surface (RIS)-assisted millimeter-wave (mmWave) multiple-input-multiple-output (MIMO) orthogonal frequency-division multiplexing (OFDM) systems. The objective is to maximize the spectral efficiency by jointly optimizing the RIS's reflection coefficients and the hybrid precoder/combiner at the base station (BS)/mobile station (MS). By resorting to classical hybrid precoder/combiner optimization techniques, this joint beamforming problem can be converted into an optimization concerning only the design of the reflection coefficients. Nevertheless, the objective function of the resulting passive beamforming problem does not have an explicit expression of the reflection coefficients. To address this difficulty, the inherent structure of the effective channel is exploited, based on which an approximation of the truncated singular value decomposition (SVD) of the effective channel is obtained, and a favorable propagation environment can be realized by directly manipulating the singular values of the effective channel. Simulation results show that the proposed method can configure a favorable channel with a small condition number. Moreover, the proposed method presents a clear performance advantage over state-of-the-art algorithms, while with a low computational complexity.